Effect of cover crops mixtures on weed suppression capacity in a dry sub-humid environment of Argentina - Malaspina, Micaela (2024)
Cover crops (CC) are increasingly used worldwide within integrated weedmanagement scenarios. They are usually established between twocommercial crops and are not harvested, grazed, or incorporated into thesoil, but remain on the surface during their growth cycle. The aim of this workwas to determine the performance of different CC mixtures and their effects onweed suppression in the south-central region of Buenos Aires province,Argentina. Field experiments were carried out in 2019 and 2020 at the CEIBarrow (MDA-INTA, Tres Arroyos), where both binary and ternary CC mixtureswere evaluated. Binary mixtures consisted of winter cereals (Avena sativa,Secale cereale) and legumes (Vicia villosa, Vicia sativa) while ternary mixtureswere obtained by combining binary mixtures with canola (Brassica napus).Weed emergence counting was performed on a 14- day basis to determineweed total density. Vegetation cover of the CC mixtures as well as biomassproduction from crops and weeds were estimated. The specific composition ofthe mixtures showed a greater influence on vegetation cover than on biomassproduction, which would depend mainly on the prevailing environmentalconditions. The type of vetch used, the addition of canola, as well as, theproportion of cereals in the mixture determined the CC effect on weeds. CCwere consistently more effective in suppressing weed biomass than seedlingemergence density. However, weed seedling suppression by CC was similar toor even greater than the chemical-based control (p<0.0001). The averagebiomass of weeds in all CC (pooled data) was highly reduced whencompared to the weedy control (12 vs 259 g m-2, p<0.001), and similarresponses were obtained when compared to the chemical fallow (8 g m-2).The mixture S. cereal+ V. villosa+ canola stood out for presenting the highestvalues of productivity and vegetation cover and high weed suppression. These results provide support for the choice of CC mixtures in a dry sub-humid area ofArgentina, aimed at maximizing interference with weeds and also todemonstrate their benefits in short- and long-term management. Therefore,CC implementation within crop sequences should be considered as acomplementary tool contributing to the development of more sustainablemanagement strategies.